Analysis of Antecedents of Trailblazing and Adoption of Public Policy Innovation Identified by a Systematic Literature Review - II - Glor, Eleanor D (2021)
The paper organizes and summarizes the conditions (antecedents) researchers and practitioners identified as occurring prior to trailblazing and adoption of public policy (including program) innovation, as identified in a systematic literature review. The review identified 87 relevant documents and 594 antecedents. Trailblazing of innovation is Rogers’ (1995) first two stages of adoption—innovation (invention) and early adoption (identified here as second and third adoptions in a government’s community or population). The antecedents are analyzed into grouped antecedents, factors and clusters. The most-mentioned grouped antecedents were citizen pressure, process, structure and political culture. The most-mentioned factors were innovation drivers, people, policy/process, and context. The factors were organized into clusters—external, political and internal. Based on number of mentions the literature considered the internal cluster the most important. The most-mentioned factors in external cluster were context and people; in political cluster, drivers, political context and political actors; in internal cluster, innovation process, drivers, people and internal environment. Multiples more antecedents were identified for internal cluster than the others. Lack of consistent definitions and the mixing of stages and levels in the literature has hampered understanding of antecedents and placed limitations on this study. The literature sometimes distinguished external and internal cluster; the current analysis also considers a political cluster, which is especially important to trailblazing of public policy innovations.